2012
DOI: 10.1542/peds.2011-3633
|View full text |Cite
|
Sign up to set email alerts
|

Baby-Friendly Hospital Practices and Meeting Exclusive Breastfeeding Intention

Abstract: Two-thirds of mothers who intend to exclusively breastfeed are not meeting their intended duration. Increased Baby-Friendly hospital practices, particularly giving only breast milk in the hospital, may help more mothers achieve their exclusive breastfeeding intentions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
197
3
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(220 citation statements)
references
References 21 publications
15
197
3
5
Order By: Relevance
“…Beginning breastfeeding within 1 hour of birth and not being given supplemental feedings or pacifiers were associated with achieving exclusive breastfeeding intention [17]. From previous study in Singapore, antenatal breast feeding education and postnatal lactation support significantly improves rates of exclusive breastfeeding up to six month after delivery [7,13].…”
Section: Discussionmentioning
confidence: 88%
“…Beginning breastfeeding within 1 hour of birth and not being given supplemental feedings or pacifiers were associated with achieving exclusive breastfeeding intention [17]. From previous study in Singapore, antenatal breast feeding education and postnatal lactation support significantly improves rates of exclusive breastfeeding up to six month after delivery [7,13].…”
Section: Discussionmentioning
confidence: 88%
“…[16][17][18][19][20] In-hospital provider encouragement is a likely outgrowth of Baby-Friendly requirements for staff education, but has not been studied independently to our knowledge. One study found five specific hospital practices-breastfeeding within the first hour, breast milk only, infant rooming-in, no pacifier use, and receipt of a telephone number for use after discharge-increased breastfeeding duration, but did not mention provider encouragement.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike previous studies which focused on specific clinics or small communities, [16][17][18] LAMB 2010 used a generalizable, population-based survey with more participants than most infant nutrition surveys on record. For example, LAMB garnered a representative sample of 5,302 respondents culled from one city compared to only 1,177 respondents in the Infant Feeding Practices Study II studying families nationwide.…”
Section: Strengthsmentioning
confidence: 99%
“…Supplements may alter infant bowel flora, sensitize the infant to allergens (depending on the content of the feeding and method used), interfere with maternal-infant bonding, and interfere with infant weight gain. 14,[47][48][49] There is no role for the routine supplementation of non-dehydrated infants with water or dextrose water; in fact, this practice could contribute to hyperbilirubinemia. 50 Before any supplementary feedings are begun, it is important that a formal evaluation of each mother-baby dyad, including a direct observation of breastfeeding, is completed by a provider trained in lactation.…”
Section: 1347-49mentioning
confidence: 99%